Self-resolving, benign subcutaneous emphysema after bilateral open inguinal hernioplasty: a case report - Banerjee, Divya J.; Chauhan, Himesh R. (International Surgery Journal, 2023)
Subcutaneous emphysema after surgery is commonly seen after thoracic or laparoscopic procedures but very rarely as a post-operative complication in open abdominal inguinal surgeries. Typically, if subcutaneous emphysema or abdominal crepitus is present after open abdominal surgeries it can mean grave underlying cause like hollow viscous perforation or gas gangrene which calls for prompt life-saving interventions. Here, we present a case of benign self-resolving post-operative subcutaneous emphysema after open bilateral inguinal hernioplasty with no apparent obvious underlying cause.